Characterization of steel slag by SEM-EDS, XRD, and INAA (Brazilian Journal of Radiation Sciences, 2021)
Steel slag is considered a by-product of the steel industry and its reuse is a strategy for environmental protection, since it consists of potential polluting materials. Its main applications involve the use of large quantities of the raw material, but the extraction of ores in smaller proportions can be attractive. For example, magnetite (Fe3O4) may be of great interest for its magnetic properties in the production of composites with different applications. On the other hand, rare earth elements (REE) production is vital for new technologies and since traces of the different REE are found in most iron ores, their extraction can be conducted together. However, previous characterization of the slag is necessary; since they vary in mineralogical composition conform to steelmaking operations. Classical characterization techniques of ores such as X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM) may be limited to characterize small fractions of materials. Therefore, in this study, neutron activation analysis was used as the characterization technique to confirm the presence of iron and REE in the slag. The steel slag composite sample of the Linz-Donawitz (LD) process was collected in a steelwork localized in the Iron Quadrangle, Minas Gerais, Brazil. The steel slag sample was characterized by instrumental neutron activation analysis (INAA), using the nuclear research reactor TRIGA MARK I IPR-R1. The results are compared with the characterizations made with XRD and SEM-EDS. Although XRD and EDS results indicated the presence of magnetite in a small proportion, INAA was decisive confirming the presence of REE in the mineralogical composition of the composite sample collected.